Two Faces of Protein Kinase Cδ: The Contrasting Roles of PKCδ in Cell Survival and Cell Death - Alakananda Basu; Deepanwita Pal (The Scientific World Journal)
Protein kinase Cδ (PKCδ) is a member of the PKC family that plays a critical role in the regulation of various cellular processes, including cell proliferation, cell death, and tumor promotion. Since the identification that PKCδ is a substrate for caspase-3, there has been overwhelming literature that linked PKCδ with proapoptotic signaling. While PKCδ generally functions as a proapoptotic protein during DNA damage-induced apoptosis, it can act as an antiapoptotic protein during receptor-initiated cell death. PKCδ has also been implicated in tumor suppression as well as survival of several cancers. The function of PKCδ depends on various factors, including its localization, tyrosine phosphorylation, and the presence of other pro- and antiapoptoic signaling molecules. This review discusses the current literature on the contrasting roles of PKCδ in cell survival and cell death.